Bombay islam: the religious economy of the west indian ocean - "Green, Nile" (New Delhi, 2011)
As a thriving port city, nineteenth-century Bombay attracted migrants from across India and beyond. Nile Green's Bombay Islam traces the ties between industrialization, imperialism and the production of religion to show how Muslim migration from Bombay fueled demand for a wide range of religious suppliers.
Keywords: Internal migrants-India Bombay-History